PENGARUH PENEMPATAN KARYAWAN DAN LOYALITAS KARYAWAN TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Kntor Hotel Dafam Pekanbaru) - Wasalwa, Manna; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much influence the placement of employees and employee loyalty to the employee performance of the Hotel office Dafam.This research was conducted at Dafam Hotel Pekanbaru which located in street sultan syarif qasim kav.150, Pekanbaru.Samples in this study were taken as many as 48 respondents and tcnhniques used census. The data in this study using survey method troughtquestionnaires filled by employees of the office. Data were obtained using simple regression analysis an mutiple regression analysis.The results of thid study indicate employee placement and employee loyalty affect the performance of employees of the office. And simultaneously employee placement and employee loyalty affect the performance of employees. Subsequent research is suggested to use other methods in examining the performance of other employees, for example through in-depth interviews of respondent.Keywords : employee placement, employee loyalty and employee performance.